Коварная дама треф: [роман] / Вячеслав Белоусов - Белоусов Вячеслав Павлович (Остросюжет)
Экземпляры: аб. (2012) / Инвентарный номер: 54008 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6